2016
DOI: 10.1007/s10616-016-0003-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of medium-chain fatty acids on the structure and immune response of IPEC-J2 cells

Abstract: Medium-chain fatty acids (MCFAs) have been suggested as an alternative to the use of antibiotics in animal nutrition with promising results. First, we studied the sensitivity of Salmonella Enteritidis and an enteropathogenic Escherichia coli strain against caprylic (C8), capric (C10) and lauric (C12) acids. A porcine in vitro model using the porcine cell line IPEC-J2 was used to test the effects of MCFAs on structural and immunological traits without and with a concomitant challenge with E. coli or S. Enteriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…It has been suggested that orally administered GML could be useful for reducing gut inflammation in vivo [46]. MCFAs, namely caprylic (C 8 ), capric (C 10 ), and lauric (C 12 ) acids, have also been shown to improve the immune responses of a porcine intestinal cell line in vitro [48].…”
Section: Immunomodulatory Activitymentioning
confidence: 99%
“…It has been suggested that orally administered GML could be useful for reducing gut inflammation in vivo [46]. MCFAs, namely caprylic (C 8 ), capric (C 10 ), and lauric (C 12 ) acids, have also been shown to improve the immune responses of a porcine intestinal cell line in vitro [48].…”
Section: Immunomodulatory Activitymentioning
confidence: 99%
“…A human in vitro cell culture experiment, employing the colonic HT-29/B6 cell line, has revealed the cellular mechanisms involving the selective removal of claudin-5 and tricellulin from the TJ [8]. Recent in vitro experiments have provided evidence of the antibacterial effect of caprate in porcine epithelial cells when challenged with Salmonella enteritidis or an enteropathogenic Escherichia coli strain [35]. Furthermore, caprate has also been shown to reduce body fat and therefore, body weight [36].…”
Section: Discussionmentioning
confidence: 99%
“…IPEC-J2 cells (ACC 701) obtained from the DSMZ (German Collection of Microorganisms and Cell Cultures, Braunschweig, Germany) and stored at our institute, were grown in plastic flasks (Greiner Bio-One International GmbH, Kremsmünster, Austria) at 37 • C in an atmosphere of 5% CO 2 , and maintained in Dulbecco's MEM/Ham's F-12 (DMEM) (Biochrom GmbH, Berlin, Germany) supplemented with 5% foetal calf serum, 100 units penicillin/mL and 100 mg streptomycin/mL (Biochrom GmbH, Berlin, Germany), as previously described [18]. The cells from passage 43 to 62 were used for the experiments.…”
Section: Ipec-j2 Cell Culture Conditionsmentioning
confidence: 99%